Social capital and self-employment of persons with disabilities (PWDs): mediation role of self-efficacy - Mahadih Kyambade; Gerald Kaliisa; Felister Birungi; Monica Tushabe (Cogent Social Sciences, 2024)
This study aims to address the research gap in understanding the mediation of self-efficacy in the relationship between social capital and self-employment among persons with disabilities. While previous research has explored the individual roles of self-efficacy, social capital, and self-employment within this population, limited attention has been paid to the specific mechanisms by which self-efficacy mediates the influence of social capital on self-employment outcomes. This study employs quantitative surveys to capture the relationships between self-efficacy, social capital, and self-employment outcomes. 106 Participants included individuals with diverse disabilities, backgrounds, and entrepreneurial experiences recruited through disability support organizations, entrepreneurship networks, and online platforms, especially those supported by the National Union of Disabled Persons of Uganda (NUDIPU). The data collected were analyzed using PROCESS MACRO to examine the direct and indirect effects of social capital on self-employment outcomes mediated by self-efficacy beliefs. The findings of this study provide insights into the mechanisms underlying disability entrepreneurship and inform the development of targeted interventions and policies to support economic empowerment and inclusion of persons with disabilities. By understanding how social capital influences individuals’ self-efficacy beliefs and motivations to pursue self-employment, this study contributes to a more comprehensive understanding of disability entrepreneurship and informs efforts to promote economic independence and empowerment within this population.